2013
DOI: 10.15288/jsad.2013.74.714
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Athletic Participation and Nonmedical Adderall Use: An Exploratory Analysis of a Performance-Enhancing Drug

Abstract: ABSTRACT. Objective: A primary motive for adolescents and young adults to nonmedically use prescription stimulants is to help them study. Adolescents and young adults are using prescription stimulants, such as Adderall (amphetamine aspartate, amphetamine sulfate, dextroamphetamine saccharate, dextroamphetamine sulfate), as performance enhancers in certain social domains, including academics and sports. The purpose of this exploratory study was to examine the nonmedical use of Adderall (a commonly prescribed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…In addition, the present review suggests that adolescents and adults are more likely to misuse short-acting or immediate-release agents compared with long-acting agents 84,97. Consistent with previous studies, the present review suggests that students who are white, affiliated with a fraternity or sorority, engaging in other illicit drugs, and male, are more likely to misuse prescription stimulants 47,49,56,57,84,89,92,94,96,101,102,113,118,124. Although some of the studies reported no sex differences, recently Weyandt et al45 reported on the effect sizes of sex differences in studies examining stimulant misuse.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the present review suggests that adolescents and adults are more likely to misuse short-acting or immediate-release agents compared with long-acting agents 84,97. Consistent with previous studies, the present review suggests that students who are white, affiliated with a fraternity or sorority, engaging in other illicit drugs, and male, are more likely to misuse prescription stimulants 47,49,56,57,84,89,92,94,96,101,102,113,118,124. Although some of the studies reported no sex differences, recently Weyandt et al45 reported on the effect sizes of sex differences in studies examining stimulant misuse.…”
Section: Discussionsupporting
confidence: 90%
“…Although the findings from this study cannot determine why former lacrosse participants are at a greater risk for potential drug use disorders, initiation or continued use of illicit drugs may be more susceptible among lacrosse players due to factors like performance enhancement (i.e., illicit use of prescribed stimulants to increase energy or focus on the playing field), 16 pain management (i.e., illicit use of prescribed opioids to manage pain from injuries), 15 or factors motivated by the stress of competition (i.e., illicit substance use to relax). 9 These findings indicate the need for additional research, and suggest that closer scrutiny of both male and female adolescent lacrosse players may be warranted in order to understand the drug related practices embedded in this particular sporting culture.…”
Section: Discussionmentioning
confidence: 82%
“…In a recent survey of nearly 21,000 students in grades 8-10 in the USA, an increased use of amphetamines was seen among males who participated in lacrosse (adjusted odds ratio 2.52) and wrestling (adjusted odds ratio 1.74) [59]. In contrast, no association among females and sporting type was found for amphetamine use.…”
Section: Amphetamines and Stimulantsmentioning
confidence: 95%